Antimicrobial Resistance and Neisseria gonorrhoeae Multiantigen Sequence Typing Profile of Neisseria gonorrhoeae in New Delhi, India. Issue 8 (August 2016) - Mahajan, Neeraj; Sood, Seema; Singh, Rajendra; Kapil, Arti; Das, Bimal Kumar; Sreenivas, Vishnubhatla; Kar, Hemanta Kumar; Sharma, Vinod Kumar
Abstract : Abstract: Molecular epidemiology of 100 consecutive gonococcal isolates collected between April 2010 and October 2013 from New Delhi was investigated using Neisseria gonorrhoeae multiantigen sequence typing (NG-MAST) along with its association with antimicrobial resistance profiles. Neisseria gonorrhoeae isolates were assigned into 60 different sequence types and 43 (71.6%) were novel. Sole representation was seen in 76.6% sequence types. There was significant association between ST6058 and resistance to penicillin ( P = 0.00) and tetracycline ( P = 0.002). Abstract : The present study highlights a heterogeneous gonococcal population in New Delhi, India. It also reveals a significant association between penicillin and tetracycline resistance in Neisseria gonorrhoeae and ST6058, the most prevalent sequence type.